Into the unknown: Do people in low literacy rate areas practise digital reading? - Samsuddin, Samsul Farid; Mohamed Shaffril, Hayrol Azril; Mohamed, Nor Aini; Bolong, Jusang (Malaysian Journal of Library and Information Science, 2021)
Various initiatives have been taken to bridge the urban-rural digital divide in Malaysia, which has impacted the change of mindset among the rural community in terms of acceptance and assimilation of digital technologies in their daily life. This includes digital literacy-related activities for self-development, especially in cultivating reading habits. The main purpose of this study is to investigate digital reading practices among rural communities in low literacy rate areas in promoting reading culture in Malaysia under the 10-year National Reading Decade (DMK) 2021-2030 programme. A quantitative design of the study which involved 400 rural community respondents from 4 selected states in Malaysia (Kedah, Kelantan, Sarawak, and Sabah) using the multi-stage and mixed sampling method in administering the survey questionnaires. This study found that rural communities in low literacy rate areas in Malaysia did practice digital reading, primarily on smartphone. The empowerment of digital literacy in terms of digital reading practices is believed to be able to narrow down the digital divide among rural communities. The findings are expected to provide useful guidance for rural development in ICT and create better understanding and awareness among policymakers to create a rural society which is learned and well-informed through a more inclusive digital reading practices.